Measurements and models of the temperature change of water samples in sea‐surface temperature buckets. (7th July 2017) - Carella, G.; Morris, A. K. R.; Pascal, R. W.; Yelland, M. J.; Berry, D. I.; Morak‐Bozzo, S.; Merchant, C. J.; Kent, E. C.
Abstract : Uncertainty in the bias adjustments applied to historical sea‐surface temperature (SST) measurements made using buckets are thought to make the largest contribution to uncertainty in global surface temperature trends. Measurements of the change in temperature of water samples in wooden and canvas buckets are compared with the predictions of models that have been used to estimate bias adjustments applied in widely used gridded analyses of SST. The results show that the models are broadly able to predict the dependence of the temperature change of the water over time on the thermal forcing and the bucket characteristics: volume and geometry; structure and material. Both the models and the observations indicate that the most important environmental parameter driving temperature biases in historical bucket measurements is the difference between the water and wet‐bulb temperatures. However, assumptions inherent in the derivation of the models are likely to affect their applicability. We observed that the water sample needed to be vigorously stirred to agree with results from the model, which assumes well‐mixed conditions. There were inconsistencies between the model results and previous measurements made in a wind tunnel in 1951. The model assumes non‐turbulent incident flow and consequently predicts an approximately square‐root dependence on airflow speed. The wind tunnel measurements, taken over a wide range of airflows, showed a much stronger dependence. In the presence of turbulence the heat transfer will increase with the turbulent intensity; for measurements made on ships the incident airflow is likely to be turbulent and the intensity of the turbulence is always unknown. Taken together, uncertainties due to the effects of turbulence and the assumption of well‐mixed water samples are expected to be substantial and may represent the limiting factor for the direct application of these models to adjust historical SST observations. Abstract : Because the sea surface is typically warmer than the air above, sea‐water samples taken with buckets typically lose heat, as shown in the image. Measurements of the temperature change in buckets similar to those used historically are compared with the output of models used to estimate bias adjustments applied in gridded analyses of sea‐surface temperature. Uncertainties in the model assumptions are explored and the results should lead to improved estimates of uncertainty on estimates of global temperature changes.